A Practical Perspective on Human Capital Post Merger Integration in Central and Eastern Europe - Sebastian-Madalin MUNTEANU; Marian-Adrian GROSU (Revista de Management Comparat International)
Driven by a philosophy of shareholder value, mergers and acquisitions form a new economic, social and cultural environment. It is only by a profound understanding of the success factors in mergers and acquisitions that they are able to improve transaction management and create new economic values. In this paper we focus on the perception of employees on a merger or acquisition, the impact it has on the new organization and what should be further done by the management team in order to ensure that critical employees are kept within the organization. We present a survey among 146 companies in 6 countries from Central and Eastern Europe that have experienced mergers or acquisitions in the last 5 years, in which we exhibit a comprehensive view of employees’ satisfaction on different hierarchical and demographic levels on the success of integration. In addition, this report includes information on risks identified that need to be addressed in the forthcoming period, especially by the organizations included in this survey, to cover areas that have been overlooked or that have been insufficiently addressed in the run to integrate faster.